2020
DOI: 10.1186/s12963-020-00220-5
|View full text |Cite|
|
Sign up to set email alerts
|

The cross-sectional average length of healthy life (HCAL): a measure that summarizes the history of cohort health and mortality

Abstract: Background: Healthy life years have superseded life expectancy (LE) as the most important indicator for population health. The most common approach to separate the total number of life years into those spent in good and poor health is the Sullivan method which incorporates the health dimension to the classic period life table, thus transforming the LE indicator into the health expectancy (HE) indicator. However, life years derived from a period life table and health prevalence derived from survey data are base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…In terms of HLY, the period life table links together the age-specific health and mortality information from individuals with substantially different set of historical conditions and behaviors ( Guillot & Canudas-Romo, 2006 ; Vaupel et al, 1979 ; Luy et al, 2020 ). From a conceptual point of view, it is therefore more reasonable to study health and mortality from a cohort perspective ( Guillot, 2011 ; Sauerberg et al, 2020 ). This holds in particular for the case of education because educational expansion is mostly a cohort-based phenomenon and its progress differs between countries.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of HLY, the period life table links together the age-specific health and mortality information from individuals with substantially different set of historical conditions and behaviors ( Guillot & Canudas-Romo, 2006 ; Vaupel et al, 1979 ; Luy et al, 2020 ). From a conceptual point of view, it is therefore more reasonable to study health and mortality from a cohort perspective ( Guillot, 2011 ; Sauerberg et al, 2020 ). This holds in particular for the case of education because educational expansion is mostly a cohort-based phenomenon and its progress differs between countries.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a technical advantage to estimating HLE by educational attainment. HLE levels and trends have been shown to be particularly sensitive to the underlying prevalence data, as opposed to mortality information (Sauerberg, Guillot and Luy 2020). In other words, the reliability of HLE estimates depends mostly on the accuracy of prevalence data.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, researchers have been working to better harmonize health data in order to measure population health across Europe more accurately (Bogaert et al 2018, Jagger andRobine 2011). Further, Luy et al (2020) show that variations in summary indicators such as LE or HLE do not necessarily reflect actual health and mortality differences over time or across countries. This is because several effects may potentially distort the comparability of HLE estimates, which particularly concerns population heterogeneity.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, health is a stock variable sensitive to past experience (Barendregt et al 1997;Brouard/Robine 1992;Murray et al 2002) and with a complex interaction between health and mortality, making it diffi cult to accurately model age-specifi c health prevalence (Riffe et al 2016(Riffe et al , 2017. In this regard, it has been shown that some relational models provide a good fi t for modelling some types of disabilities by age (Marshall et al 2013), while alternative summary measures that incorporate the mortality history of cohorts and therefore combine health and mortality information have also been proposed (Sauerberg et al 2020). However, these methods are more important to capture the relationship between age-specifi c prevalence of disability and various disability types rather than to harmonise and extrapolate prevalence at older ages.…”
Section: Figurementioning
confidence: 99%